2004
DOI: 10.1074/jbc.m401646200
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Nucleic Acid Structure and Stability Modulates the Efficiency of Minus-Strand Transfer Mediated by the HIV-1 Nucleocapsid Protein

Abstract: During human immunodeficiency virus type 1 minusstrand transfer, the nucleocapsid protein (NC) facilitates annealing of the complementary repeat regions at the 3-ends of acceptor RNA and minus-strand strong-stop DNA ((؊) SSDNA). In addition, NC destabilizes the highly structured complementary trans-activation response element (TAR) stem-loop (TAR DNA) at the 3-end of (؊) SSDNA and inhibits TAR-induced self-priming, a deadend reaction that competes with minus-strand transfer. To investigate the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
85
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 89 publications
8
85
0
Order By: Relevance
“…Secondary structure predictions by mFold (48,49) of A97h(30A) and A97h(30R) indicated that they folded into different, lower stability structures than the wild-type A97h. It has been reported that presence of a secondary structure in acceptor RNA reduces transfer efficiency, and removal of structure promotes transfer (19,30). Therefore, it is likely that structural changes made to construct the bipartite acceptors made them more effective for transfer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary structure predictions by mFold (48,49) of A97h(30A) and A97h(30R) indicated that they folded into different, lower stability structures than the wild-type A97h. It has been reported that presence of a secondary structure in acceptor RNA reduces transfer efficiency, and removal of structure promotes transfer (19,30). Therefore, it is likely that structural changes made to construct the bipartite acceptors made them more effective for transfer.…”
Section: Discussionmentioning
confidence: 99%
“…For the acceptor template, secondary structure predictions by mFold (48,49) indicated the R region of the acceptor could form altered structures as varied lengths of U3 were attached, leading to different transfer efficiencies. This result suggests the structure and stability of the R region of the acceptor could also be influenced by regions outside of those directly involved in the base pairing associated with the long-transfer (30). Reverse transcription in HIV-1 is initiated by a tRNA Lys-3 primer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[124][125][126][127][128][129][130][131][132][133][134][135][136] This chaperone activity, facilitating restructuring of the nucleic acid complex, has been attributed to both an aggregating ability of NC and a facility for duplex destabilization. 125,131,[137][138][139][140][141][142][143][144][145] This destabilization, however, is weak, 143,144,146,147 and will not completely melt DNA without a complementary strand. 6,138,148,149 Stretching and relaxation cycles can also reveal information on the kinetics of protein association and dissociation.…”
Section: Figure 11mentioning
confidence: 99%
“…Studies have shown that all these three steps need the participation of NC proteins, especially the minus stand transfer step. 66,[78][79][80] The effect of NC's chaperone activity on these processes is detailed in the review by Levin and Musier-Forsyth in this special issue.…”
Section: Na Chaperone Proteins: Retroviral Nc Proteinsmentioning
confidence: 99%